Peer Connect for African American breast cancer survivors and caregivers: a train-the-trainer approach for peer support - Allicock, Marlyn (Transl Behav Med, 2017)
Racial disparities in breast cancer survivorship are a major concern nationally. How survivors cope with cancer and re-frame their lives is a critical part of survivorship. Community-academic research partnerships may facilitate access to much-needed psychosocial support for African American survivors and caregivers in rural areas, but drivers of successful intervention implementation are not well understood. The purpose of this study was to describe the training and evaluation of Community Coaches and Guides (i.e., peer supporters) using the Peer Connect program for African American breast cancer survivors and caregivers. Community engagement strategies were used to implement the training component of Peer Connect, an evidence-based program grounded in the Diffusion of Innovation Theory utilizing motivational interviewing techniques (MI) and a “train-the-trainer” model. Quantitative and qualitative methods examined implementation outcomes of feasibility, MI fidelity, and acceptability—precursor outcomes that must be achieved before examining intervention impact vis-à-vis changes in support care. Training was feasible to implement and replicable by the trained Community Coaches. Beyond feasibility and replicability, success was modest regarding MI fidelity. Benefits (e.g., serving as role models and having safe sources of support) and lessons learned (e.g., need for additional quality control) were identified as both facilitators and barriers to implementation and as factors that could impact the effectiveness of community-engaged programs to improve survivorship outcomes. Peer Connect, like other programs that employ community-engagement strategies, holds promise to meet the psychosocial support needs of diverse rural cancer survivor populations.